Prediction of Critical Temperatures and Critical Pressures of Some Industrially Relevant Organic Substances from Rather Simple Topological Descriptors - Duchowicz, Pablo Román (2002)
The simplest topological molecular parameters were applied to predict critical temperatures and critical pressures in terms of the QSAR/QSPR theory. Through the development of four different calculation schemes, the convenience of using the atomic coordination numbers for different atoms and the corresponding identity of chemical bonds was shown. A satisfactory agreement between the theoretical and experimental data was attained. Some limitations of the proposed approach are pointed out.